Accreditation as Instrument Cultivating Quality: A Review Literature on Islamic Education - Ahmad Suryana; Yesi Susilawati; Masripah Masripah; Annisa Mayasari (UIN Siber Syekh Nurjati Cirebon, 2026)
Accreditation is instrument guarantee quality externally intended For ensure and encourage improvement quality institution education. In the context of Islamic education, practice accreditation Still often understood as an administrative process that is oriented towards fulfillment instruments and achievements value, so that Not yet fully contribute to the formation of culture sustainable quality. Research This aim reconstruct role accreditation as instrument cultivation quality through approach qualitative with Systematic Literature Review (SLR) design. Research data in the form of document scientific secondary data obtained from journal academic, books, and document policies, which are traced through the Google Scholar, DOAJ, and Garuda databases. Selected literature analyzed using content analysis and thematic analysis to identify pattern findings, gaps studies, as well as connection conceptual between accreditation and culture quality.Study results show that quality education demand transformation system organization and internalization mark quality in practice institutional accreditation reform based performance open opportunity strengthening quality, but its implementation Still hampered by orientation administrative and not yet optimally integration standard quality to in culture Work institution. Synthesis literature produce a conceptual model that places accreditation as trigger change culture organization through internalization standard performance, change habit work, until formation culture quality sustainable. Contribution study This lies in strengthening perspective accreditation as a cultural driver in management quality Islamic education, as well as recommend reorientation meaning accreditation at the level institution as well as development study empirical advanced For test the resulting conceptual model.Keywords : accreditation education , culture quality , Islamic education